Functional disulphide bonds: methods and protocols - Hogg, Philip J. (Methods in molecular biology, 2019)
1. Classification of protein disulfide bonds -- 2. Assessing the evolutionary conservation of protein disulphide bonds -- 3. A proteomics workflow for the Identification of labile disulphide bonds at the cell surface -- 4. Quantification of the redox state of protein disulfide bonds -- 5. Quantification of the redox state of protein disulfide bonds -- 6. Studying functional disulfide bonds by computer simulations -- 7. Dynamic force spectroscopy analysis on the redox states of protein disulfide bonds -- 8. Assays of thiol isomerase enzymatic activity -- 9. Functional assays of thiol isomerase ERp5 -- 10. IDENTIFICATION OF PDI SUBSTRATES BY MECHANISM-BASED KINETIC TRAPPING -- 11. Site-specific proteomic mapping of modified cysteine residues -- 12. Quantitation of glutathione, glutathione disulfide and protein-glutathione mixed disulfides by high performance liquid chromatography-tandem mass spectrometry -- 13. Interrogation of Functional Mitochondrial Cysteine Residues by Quantitative Mass Spectrometry -- 14. Oxidative Protein Folding Using trans-3,4-Dihydroxyselenolane Oxide -- 15. Methodology for identification of the cysteine-reactive covalent inhibitors -- 16. In Vivo Measurement of Redox-Regulated TG2 Activity -- 17. Quantitation of total and free thiol β2-glycoprotein I levels for diagnostic and prognostic purposes in the antiphospholipid syndrome -- 18. Quantitation of total and free thiol angiotensinogen as a prognostic marker for pre-eclampsia -- 19. Preparation of a dithiol-reactive probe for PET imaging of cell death -- 20. Flow Cytometry Assessment of Procoagulant Platelets Using A Dithiol Reactive Probe